2022
DOI: 10.3389/fvets.2022.959449
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and antioxidant effects of Glycyrrhiza uralensis polysaccharide in Lohmann Brown chickens

Abstract: Glycyrrhiza polysaccharide extract 1 (GPS-1) is a bioactive component isolated from Glycyrrhiza uralensis, also known as Chinese licorice. It appears to be pharmacologically active as an antibacterial, antiviral, and anti-tumor agent. GPS-1 has also been shown to buffer liver health and regulate the immune system. Moreover, GPS-1 is low cost and easy to extract. More study was needed to elucidate the biochemical pathways underlying the immunomodulatory and antioxidant benefits observed in Glycyrrhiza polysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…It is currently believed that this result is due to the suppression of hydroperoxide production (67). Previous studies have demonstrated that GP has a notable ability to scavenge free radicals, including DPPH, hydrogen peroxide, ABTS, and superoxide anion radicals (19), which well explains our findings. Notably, the maximum TBARS value in fresh meat is 1.0 mg MDA/kg (68), yet the shown TBARS values in our study were all above 2.0 mg MDA/kg.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is currently believed that this result is due to the suppression of hydroperoxide production (67). Previous studies have demonstrated that GP has a notable ability to scavenge free radicals, including DPPH, hydrogen peroxide, ABTS, and superoxide anion radicals (19), which well explains our findings. Notably, the maximum TBARS value in fresh meat is 1.0 mg MDA/kg (68), yet the shown TBARS values in our study were all above 2.0 mg MDA/kg.…”
Section: Discussionsupporting
confidence: 90%
“…At 42 d of the trial, when the GP supplementation exceeded 1,000 mg/kg, there was a significant increase in GLB concentration, suggesting that GP might affect the immune function of broilers in the later stages of growth. Zhou et al had reported that GP significantly enhanced the serum antibody titer in Lohmann Brown chickens, promoted the development of immune organs and proliferation of immune cells and stimulated lymphocytes and dendritic cells to secrete relevant cytokines (19). Wu et al (48) demonstrated that the synergistic effect of GP with the NDV vaccine in chickens led to the production of an increased number of Newcastle disease antibodies, which held significant importance in the prevention of Newcastle disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its complex chemical structure makes it have many functions. It has been proven to enhance and regulate the body's immunity [ 7 ], be antibacterial [ 8 ], inhibit tumor growth [ 9 ], have antioxidant and other effects [ 10 ], and is often widely used as a feed additive in the aquaculture industry. In addition, it also has a strong antiviral effect and can significantly inhibit the invasion and proliferation of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Liu studied the antibacterial activity of licorice extract, and found that oleic acid, dehydrocyrrhizin D, glycyrrhetinic acid had a good inhibitory effect on Streptococcus mutans, Escherichia coli, Bacillus subtilis and other bacteria [ 17 ]. Recent studies have found that GTF have good anti-inflammatory, antibacterial and antiviral effects [ 18 , 19 , 20 ]. However, there has been no relevant report on whether GTFs have an antibacterial effect on tilapia Streptococcus.…”
Section: Introductionmentioning
confidence: 99%